Surgical management of peri-implantitis in adjunction with BlueM oxygen therapy: a case report with 5-years follow-up - Tanka, Karel; Alshehri, Fahad Ali (International Journal Of Community Medicine And Public Health, 2023)
Peri-implantitis is an inflammatory disease associated with plaque accumulation in peri-implant tissues, and can cause implant failure. Several surgical and nonsurgical protocols have been proposed to treat patients with peri-implantitis. In this case report, we describe the surgical management of peri-implantitis with the use of BlueM oxygen therapy after mechanical debridement of dental implant surface. Although, several conventional anti-infective modalities have been employed to treat peri-implantitis, the application of topical oxygen therapy can be very effective. The case demonstrated good results with the maintenance of peri-implant bone level and absence of clinical signs of inflammation.